Biogas production from sugar beet and maize at various total solid contents - Bayır, Zeynep. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2009., 2009)
Nowadays, energy required in almost all fields of everyday life is provided mostly by expensive imported energy sources in Turkey. In order to meet the increasing demand of energy, it is indispensable to find alternative sources. Research activities on the biogas production by using energy crops are becoming attractive research area due to abundant availability of the crops in Turkey in addition to the reasons mentioned above. The objective of this study was to evaluate the performance of biogas production system using sugar beet and maize as substrates. Additionally, the optimum total solid content at which the most efficient biogas production took place was investigated for each crop. For this purpose, eleven different lab-scale digesters which were loaded with energy crops were monitored regularly. Anaerobically digested granular sludge was also added to the reactors and the digesters were placed in a temperature controlled water bath. During the experiments which were carried out by using maize as a substrate, the effect of inoculum to substrate ratio on the biogas production efficiency of the system was also investigated. The results confirmed that the digester including maize and seeding sludge at 12 % total solid content with an inoculum to substrate ratio (I/S) of 1.5 performed the most efficient digestion process with regard to its biogas production, methane yield and biogas yield. On the other hand, methane generation could not be observed for the reactor including the same amount of total solid content but using the lower inoculum to substrate ratio of 1. This conclusion was attributed to high levels of VFA generated as a result of biological decomposition. The amount of seeding sludge was found to be insufficient to neutralize the negative effects of organic acids which were formed by degradation of high concentrations of organic matter contained in the reactor.
Keywords: Biogas -- Research -- Turkey.; Biogas -- Turkey.